Audio Production Basics with Cubase 10.5 - Cook, Frank D.; Glynn, Harley (Rowman & Littlefield Publishers, 2020)
Learn the basics of recording, editing, and mixing audio using Cubase Elements, Artist, or Pro. Experience the software used worldwide by musicians, producers, engineers, mixers, and audio professionals. Filled with tips and insights, Audio Production Basics with Cubase 10.5 will get you working fast. With this book and the included media files, you’ll get the practical, hands-on exposure you need. We cover everything from setting up your computer to the fundamentals of audio production, including: Basic Digital Audio Workstation operations and audio hardware options Principles of sound production and microphone use Essential Cubase concepts and operations MIDI fundamentals for playing and performing with virtual instruments Multi-track recording Plug-in use and signal processing techniques Mixing your project and using automation Outputting your final mixdown Cubase software is very powerful, yet fun and easy to use. Everything you learn here will apply to all editions of Cubase (Elements, Artist, and Pro), so you can easily upgrade in the future no matter where you are starting today. Take the first step now, with Audio Production Basics with Cubase 10.5.